2020
DOI: 10.1101/2020.12.01.20241877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of social distancing regulations and epidemic risk perception on social contact and SARS-CoV-2 transmission potential in rural South Africa: analysis of repeated cross-sectional surveys

Abstract: BackgroundSouth Africa implemented rapid and strict physical distancing regulations to minimize SARS-CoV-2 epidemic spread. Evidence on the impact of such measures on interpersonal contact in rural and lower-income settings is limited.MethodsWe compared population-representative social contact surveys conducted in the same rural KwaZulu-Natal location once in 2019 and twice in mid-2020. Respondents reported characteristics of physical and conversational (‘close interaction’) contacts over 24 hours. We built ag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…This review attempted to assess the overall effectiveness of the public health intervention packages by reporting the percentage difference in outcome before and after implementation of measures or between regions or countries studied. Eleven of the 37 included studies noted a difference of between 26% and 50% in transmission of SARS-CoV-2 and incidence of covid-19,7172737475767778798081 nine noted a difference of between 51% and 75% in SARS-CoV-2 transmission, covid-19 incidence, and covid-19 mortality,828384858687888990 and 14 noted a difference of more than 75% in transmission of SARS-CoV-2, covid-19 incidence and covid-19 mortality 808190919293949596979899100101. For the remaining studies, the overall effectiveness was not assessed owing to a lack of comparators (see supplementary material 3, table 3).…”
Section: Resultsmentioning
confidence: 99%
“…This review attempted to assess the overall effectiveness of the public health intervention packages by reporting the percentage difference in outcome before and after implementation of measures or between regions or countries studied. Eleven of the 37 included studies noted a difference of between 26% and 50% in transmission of SARS-CoV-2 and incidence of covid-19,7172737475767778798081 nine noted a difference of between 51% and 75% in SARS-CoV-2 transmission, covid-19 incidence, and covid-19 mortality,828384858687888990 and 14 noted a difference of more than 75% in transmission of SARS-CoV-2, covid-19 incidence and covid-19 mortality 808190919293949596979899100101. For the remaining studies, the overall effectiveness was not assessed owing to a lack of comparators (see supplementary material 3, table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The majority (8/12) of studies were based in high-income countries: European countries (n=6), the United States (n=1) or both (n=1). Eight studies surveyed participants with the intention of describing contact patterns representative of an entire country 3340 and four studies aimed to describe sub-national areas such as cities (Shanghai and Wuhan in one study, Shenzhen and Changsha in a second) 41,42 , an informal settlement in Nairobi, Kenya 43 and a district in KwaZulu-Natal, South Africa 44 . Six studies included adults aged 18 years and above only 33,3537,39,43 , four studies included participants of all ages 34,4042 and two studies included teenagers and above 38,44 .…”
Section: Resultsmentioning
confidence: 99%
“…Eleven 3343 studies collected data during the initial mitigation period between February and May 2020 with the most stringent physical distancing measures (Figure 2) with seven 3335,3740 collecting data during nationally-declared lockdown and four 36,4143 during regional lockdown. Five 3436,38,42 studies also collected additional data when interventions were relaxed (April and May for China and between May and September for other settings) and one 44 study collected data exclusively during the period of relaxation 44 . Policies in place during data collection period were similar but varied (SI.6, SI.16) as did the epidemic situation (SI.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The social contact data used in our model were collected in 2019, before the start of the COVID-19 pandemic. Comparable social contact data were collected from the same study community in June-August 2020, during the pandemic, and suggested that reductions in contact time in clinics may have been smaller than reductions in other congregate locations 7 , possibly increasing the importance of transmission in clinics to overall disease burden during this period. The IPC interventions we simulated were also designed and parameterised before the start of the pandemic, and changing views on IPC may have changed the relative impact of the different interventions over longer time periods.…”
Section: Discussionmentioning
confidence: 99%